Hartmann Newtonian radiating MHD flow for a rotating vertical porous channel immersed in a Darcian Porous Regime. Issue 7 (26th August 2014) - Ahmed, Sahin; J. Chamkha, Ali
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop and correct the problem studied by Makinde and Mhone (2005) to a rotating vertical porous channel immersed in a Darcian porous regime in presence of a strong transverse magnetic filled and with the application of thermal radiation. In this investigation, the fluid is considered to be of viscous, electrically conducting, Newtonian and radiating and is optically thin with a relatively low density. Excellent agreement is obtained for exact solutions with those of previously published works. Design/methodology/approach – In this investigation, a closed form analytical method based on the complex notations for the velocity, temperature and the pressure is developed to solve the governing coupled, non-linear partial differential equations. The accuracy and effectiveness of the method are demonstrated. Findings – Interestingly observed that, the Lorentizian body force is not act as a drag force as in conventional MHD flows, but as an aiding body force and this will serve to accelerate the flow and boost the primary velocities. Due to the large rotation of the channel, the primary velocities are become flattered and shift towards the walls of the channel. With a rise in Darcian drag force, flow velocity and shear stress are found to reduce. Moreover, increasing thermal radiation and rotation of the channel strongly depress the shear stress, and maximum flow reversal, i.e. back flow is observed due to large Darcian resistance, thermal radiation and rotation. Research limitations/implications – The analysis is valid for unsteady, two-dimensional laminar flow of an optically thick no-gray gas, electrically conducting, and Newtonian fluid past an isothermal vertical surface adjacent to the Darcian regime with variable surface temperature. An extension to three-dimensional flow case is left for future work. Practical implications – Practical interest of such study includes applications in magnetic control of molten iron flow in the steel industry, liquid metal cooling in nuclear reactors, magnetic suppression of molten semi-conducting materials and meteorology and in many branches of engineering and science. It is well known that the effect of thermal radiation is important in space technology and high-temperature processes. Thermal radiation also plays an important role in controlling heat transfer process in polymer processing industry. Originality/value – The paper presents useful conclusions with the help of graphical results obtained from studying exact solutions based on complex notations for Darcian drag force, rotation of the channel and conduction-radiation heat transfer interaction by unsteady rotational flow in a vertical porous channel embedded in a Darcian porous regime under the application hydromagnetic force. The results of this study may be of interest to engineers for heat transfer augmentation and drag reduction in heat exchangers as well as MHD boundary layer control of re-entry vehicles, etc.